The Hollywood daughter [large type] : a novel - Alcott, Kate (Thorndike Press, 2017)
"In 1950, Ingrid Bergman already a major star after movies like Casablanca and Joan of Arc has a baby out of wedlock with her Italian lover, film director Roberto Rossellini. Previously held up as an icon of purity, Bergman's fall shocked her legions of American fans. Growing up in Hollywood, Jessica Malloy watches as her PR executive father helps make Ingrid a star at Selznick Studio. Over years of fleeting interactions with the actress, Jesse comes to idolize Ingrid, who she considered not only the epitome of elegance and integrity, but also the picture-perfect mother, an area where her own difficult mom falls short. In a heated era of McCarthyism and extreme censorship, Ingrid's affair sets off an international scandal that robs seventeen-year-old Jesse of her childhood hero. When the stress placed on Jesse's father begins to reveal hidden truths about the Malloy family, Jesse's eyes are opened to the complex realities of life and love."--Amazon.com